Bloody constraint : war and chivalry in Shakespeare - Meron, Theodor, 1930- (Oxford University Press, 2001)
War is a major theme in Shakespeare's plays. Aside from its dramatic appeal, it provided him with a context in which his characters, steeped in the ideals of chivalry, could discuss such concepts as honor, courage, patriotism, and justice. Well aware of the decline of chivalry in his own era, Shakespeare gave his characters lines calling for civilized behavior, mercy, humanitarian principles, and moral responsibility. In this remarkable new book, eminent legal scholar Theodor Meron looks at contemporary international humanitarian law and rules for the conduct of war through the lens of Shakesp.